Arabic, persian words in terminology of the social sciences - Zhiyekbayeva, А. В. (Journal of Oriental Studies, 2016)
This article discusses the concept of social terminology and defi nitions of Social Sciences of the Kazakh language, derived fromborrowingsfrom Arabic and Persian languages.